2014
DOI: 10.1007/s11356-014-2651-z
|View full text |Cite
|
Sign up to set email alerts
|

High levels of activity of bats at gold mining water bodies: implications for compliance with the International Cyanide Management Code

Abstract: Wildlife and livestock are known to visit and interact with tailings dam and other wastewater impoundments at gold mines. When cyanide concentrations within these water bodies exceed a critical toxicity threshold, significant cyanide-related mortality events can occur in wildlife. Highly mobile taxa such as birds are particularly susceptible to cyanide toxicosis. Nocturnally active bats have similar access to uncovered wastewater impoundments as birds; however, cyanide toxicosis risks to bats remain ambiguous.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Australian studies also indicate high levels of bat activity around bodies of water (Lumsden and Bennett 1995;Williams and Dickman 2004;Griffiths et al 2014a). Young and Ford (2000) found that species richness of bats, abundance, and capture success in the semi-arid Idalia National Park was greatest in areas adjacent to water, with 97 % of captures occurring at sites with water.…”
Section: Water Sources Used By Batsmentioning
confidence: 99%
See 2 more Smart Citations
“…Australian studies also indicate high levels of bat activity around bodies of water (Lumsden and Bennett 1995;Williams and Dickman 2004;Griffiths et al 2014a). Young and Ford (2000) found that species richness of bats, abundance, and capture success in the semi-arid Idalia National Park was greatest in areas adjacent to water, with 97 % of captures occurring at sites with water.…”
Section: Water Sources Used By Batsmentioning
confidence: 99%
“…Lisón and Calvo 2011), cattle troughs, swimming pools and settling ponds at waste water treatment facilities (Vaughan et al 1996;Abbott et al 2009;Naidoo et al 2013Naidoo et al , 2014 and mines having natural seepage Griffiths et al 2014a).…”
Section: Bodies Of Water As a Drinking Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The effects and impacts of heavy metal, chemical pollutants and other elements that bats have been and are currently exposed to is gaining increased attention (Zocche et al 2010, Gri ths et al 2014, Lovett and McBee 2015, Carrasco-Rueda et al 2020). Heavy metal pollution has been shown to affect bat ecology, genetics, physiology and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Actualmente, las plantas de tratamiento de aguas residuales que contienen cianuro emplean métodos físicos, químicos y biológicos para la descontaminación (Griffiths et al, 2014;Kaita et al, 2018;Copari, 2019). En los métodos químicos principalmente se emplea la oxidación química utilizando cloruros e hipoclorito de sodio (Watanabe et al, 1998); sin embargo, estas técnicas no degradan completamente todo el cianuro (Figueria et al, 1996).…”
Section: Introductionunclassified